Comparison of the impact of ships to size-segregated particle concentrations in two harbour cities of northern Adriatic Sea. (November 2020) - Merico, E.; Conte, M.; Grasso, F.M.; Cesari, D.; Gambaro, A.; Morabito, E.; Gregoris, E.; Orlando, S.; Alebić-Juretić, A.; Zubak, V.; Mifka, B.; Contini, D.
Abstract: Detailed information on in-harbour shipping contribution to size segregated particles in coastal cities are scarce, especially in the busy Mediterranean basin. This poses issues for human exposure and air quality in urban harbour agglomerates, where only criteria pollutants (i.e. PM10 and/or PM2.5 ) are usually monitored. In this work, particle number and mass size distributions, in a large size range (0.01–31 μm), were obtained in two coastal cities of northern Adriatic Sea: Venice (Italy) and Rijeka (Croatia). Three size ranges were investigated: nanoparticles (diameter D < 0.25 μm); fine particles (0.25<D < 1 μm), and coarse particles (D > 1 μm). Absolute concentrations were larger in Venice for all size ranges showing, using analysis of daily trends, a large influence of local meteorology and boundary-layer dynamics. Contribution of road transport was larger (in relative terms) in Rijeka compared to Venice. The highest contributions of shipping were in Venice, mainly because of the larger ship traffic. Maximum impact was on nanoparticles 7.4% (Venice) and 1.8% (Rijeka), the minimum was on fine range 1.9% (Venice) and <0.2% (Rijeka) and intermediate values were found in the coarse fraction 1.8% (Venice) and 0.5% (Rijeka). Contribution of shipping to mass concentration was not distinguishable from uncertainty in Rijeka (<0.2% for PM1, PM2.5, and PM10 ) and was about 2% in Venice. Relative contributions as function of particles size show remarkable similitudes: a maximum for nanoparticles, a quick decrease and a successive secondary maximum (2–3 times lower than the first) in the fine range. For larger diameters, the relative contributions reach a minimum at 1–1.5 μm and there is a successive increase in the coarse range. Size distributions showed a not negligible contribution of harbour emissions to nanoparticle and fine particle number concentrations, compared to PM2.5 or PM10, indicating them as a better metric to monitor shipping impacts compared to mass concentrations (PM2.5 or PM10 ). Graphical abstract: Image 1 Highlights: High temporal resolution aerosol data were collected in two Adriatic port cities. Shipping contribution to particle concentration of different sizes was investigated. Contributions to nanoparticles were significantly larger compared to other sizes. Relative contributions to nanoparticles were 7.4% in Venice and 1.8% in Rijeka. Contributions to PM1, PM2.5 and PM10 were about 2% in Venice and <0.2% in Rijeka.